2000
DOI: 10.1063/1.480651
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonicity contributions to the vibrational second hyperpolarizability of conjugated oligomers

Abstract: Restricted Hartree-Fock 6-31G calculations of electrical and mechanical anharmonicity contributions to the longitudinal vibrational second hyperpolarizability have been carried out for eight homologous series of conjugated oligomers-polyacetylene, polyyne, polydiacetylene, polybutatriene, polycumulene, polysilane, polymethineimine, and polypyrrole. To draw conclusions about the limiting infinite polymer behavior, chains containing up to 12 heavy atoms along the conjugated backbone were considered. In general, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…23 Many of the lower-order derivatives required for our treatment were obtained analytically using the GAUSSIAN 98 suite of programs. 34 These include a 20 , a 01 , a 11 , a 02 , a 12 , and a 03 at the HF level and all but the last two of this list at the MP2 level. All vibrational derivatives are computed with respect to atomic Cartesian coordinates.…”
Section: Computational Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Many of the lower-order derivatives required for our treatment were obtained analytically using the GAUSSIAN 98 suite of programs. 34 These include a 20 , a 01 , a 11 , a 02 , a 12 , and a 03 at the HF level and all but the last two of this list at the MP2 level. All vibrational derivatives are computed with respect to atomic Cartesian coordinates.…”
Section: Computational Considerationsmentioning
confidence: 99%
“…18 From a computational viewpoint NR ͑hyper͒polarizabilities can be evaluated either by means of analytical formulas 19 as they are in the BK method, or by numerical finite field ͑FF͒ techniques. 15,20,21 The FF treatment is computationally advantageous especially when used in conjunction with highly correlated electronic structure methods and/or when applied to large systems. 22 The remaining higher-order square bracket terms ͑de-noted below by C-ZPVA͒, in combination with the zeropoint vibrational averaging ͑ZPVA͒ term, collectively give rise to what has been referred to as the curvature ͑C͒ contribution 23 to the property P, i.e., P c ϭ P zpva ϩ P c-zpva .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 It has been shown that in many circumstances the corrections arising from the molecular vibrations are of similar magnitude, or even larger, than the electronic counterparts. [7][8][9][10][11][12][13][14][15][16] For systems on condensed phase the influence of the medium must also be considered, being the description of solvated systems usually made through simulation methods ͑molecular dynamics or Monte Carlo͒ or continuum models. [17][18][19][20][21][22][23] Methanol has been the subject of a number of recent theoretical and experimental investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Even for some ordinary -conjugated NLO molecules, such as 1-formyl-6-hydroxyhexa-1,3,5-triene, the perturbation series for the ab initio static vibrational hyperpolarizabilities is ͑at least͒ initially divergent. 13,20,21 Assuming that all vibrational frequencies are small compared to optical frequencies, i.e., within the infinite ͑optical͒ frequency approximation, there exists an alternative to the perturbation approach for calculating vibrational contributions [22][23][24][25] to the most important NLO processes. In this alternative finite field ͑FF͒ procedure, the total vibrational hyperpolarizability is expressed as the sum of a nuclear relaxation ͑P nr ͒ and a curvature ͑P c ͒ term.…”
Section: Introductionmentioning
confidence: 99%